Pathogenic properties of dermatophytes and it's potential in keratin degradation (Journal of Academic Research, 2022)
Dermatophytes play a major role in the degradation of animal tissues such as keratin. Keratin considered to be main component in the skin. The aim of this research was to study the mechanisms of degradation of keratin via Trichophyton mentagrophytes . T. mentagrophytes was grown on leqiud media supported by keratin azure as a source of carbon and nitrogen. Keratinolytic activities were observed by measuring the activity of keratinase (release keratin azure).The results showed that the dermatophytic fungus (T. mentagrophytes) was able to extract nutrients from the substrate. In addition, the fungus showed the highest ability to release azure in test medium.